Determinants of Stunting in Siantan Hulu Subdistrict, North Pontianak Based on Spidergram Analysis - Kurniati, Rezky; Aprillia Krisnawaty; Linda Suwarni (Sean Institute, 2023)
Stunting is a child's growth and development disorder which is characterized by a lack of nutritional intake, infection, or inadequate stimulation (WHO). Results from the Indonesian Nutrition Status Survey (INSS), the prevalence of stunted toddlers in districts/cities in West Kalimantan in 2022 reached 27.8%. The figure in Pontianak City, 19.7%, is still higher than the national figure, but has fallen from before. The national target is that the prevalence of stunting reaches 14% by 2024. The aim of this research is to determine the determinants of stunting in Siantan Hulu Village. This type of research is descriptive observational research. The number of samples in this study was 80 respondents, namely households with toddlers aged 24 - 59 months in Siantan Hulu Village. Data analysis using spidegram. The results of the analysis using spidergram showed that the determinants of stunting in Siantan Hulu Village included characteristics of toddlers, exposure to cigarette smoke, health services, immunization history and stunting IEC. Meanwhile, maternal characteristics, early initiation of breastfeeding, exclusive breastfeeding, household sanitation and water are not significant determinants of stunting in Siantan Hulu Village.